Computational Analysis of Self-Healing in Nanomaterials Using Neural Spike Algorithms - Jongho Seol; Jongyeop Kim; Abhilash Kancharla (Information)
This computational study investigates dynamic self-healing processes in nanomaterials driven by neuronal spike activity. We developed a multiscale simulation framework that integrates neuronal dynamics, quantum mechanical effects, and material science principles. Our model incorporates a time-dependent neuron spike voltage equation coupled with a nanomaterial health update function, including quantum probability terms, to capture nanoscale effects. We employ reliability engineering concepts to assess system performance. Simulations reveal that neuronal spike patterns significantly influence self-healing dynamics, exhibiting non-linear behavior with quantum effects crucial to healing efficiency. Statistical analysis demonstrates a strong correlation between spike frequency and healing rate, identifying an optimal range for maximum recovery. Integrating quantum probabilities yields more accurate nanoscale behavior predictions than classical approaches alone. This study provides a foundation for understanding and optimizing neuronal spike-induced recovery in nanomaterials with potential applications in neural interfaces, intelligent materials, and biomedical devices.